3-D OCT imaging of hyalocytes in partial posterior vitreous detachment and vaso-occlusive retinal disease - Sofia Ahsanuddin; Hernan A. Rios; Jeffrey A. Glassberg; Toco Y.P. Chui; J. Sebag; Richard B. Rosen (American Journal of Ophthalmology Case Reports, 2023)
Purpose: To describe the spatial distribution and morphologic characteristics of macrophage-like cells called hyalocytes in the posterior vitreous cortex of a patient with unilateral partial posterior vitreous detachment (PVD) using coronal plane en face optical coherence tomography (OCT). Observations: A 54-year-old male with sickle cell disease (HbSC genotype) presented with a partial PVD in one eye. Rendered volumes of a slab extending from 600 μm to 3 μm anterior to the inner limiting membrane (ILM) revealed hyperreflective foci in the detached posterior vitreous cortex suspended anterior to the macula, likely representing hyalocytes. In the fellow eye without PVD, hyperreflective foci were located 3 μm anterior to the ILM. The morphology of the cells in the eye with PVD varied between a ramified state with multiple elongated processes and a more activated state characterized by a plump cell body with fewer retracted processes. In the same anatomical location, the hyperreflective foci were 10-fold more numerous in the patient with vaso-occlusive disease than in an unaffected, age-matched control. Conclusions and Importance: Direct, non-invasive, and label-free techniques of imaging cells at the vitreoretinal interface and within the vitreous body is an emerging field. The findings from this case report suggest that coronal plane en face OCT can be used to provide a detailed and quantitative characterization of cells at the human vitreo-retinal interface in vivo. Importantly, this case report demonstrates that 3D-OCT renderings can enhance visualization of these cells in relation to the ILM, which may provide clues concerning the identity and contribution of these cells to the pathogenesis of vitreo-retinal diseases.